Significant association of elevated serum galectin-9 levels with the development of non-alcoholic fatty liver disease in patients with rheumatoid arthritis - Chen, Po-Ku; Hsu, Wei-Fan; Peng, Cheng-Yuan; Liao, Tsai-Ling; Chang, Shih-Hsin; Chen, Hsin-Hua; Chen, Chu-Huang; Chen, Der-Yuan (Frontiers in Medicine, 2024)
Background Non-alcoholic fatty liver disease (NAFLD) is prevalent among rheumatoid arthritis (RA) patients, but its pathogenesis has rarely been explored. Galectin-9 (Gal-9) interacts with T cell immunoglobulin and mucin-containing-molecule-3 (TIM-3) expressed on hepatocytes and thus regulates T cell proliferation in a murine model of NAFLD. We aimed to examine the pathogenic role of the Gal-9/TIM-3 pathway in RA-NAFLD. Methods Serum levels of Gal-9, soluble TIM-3 (sTIM-3), fatty acid-binding proteins (FABP)1, and FABP4 were determined by ELISA in forty-five RA patients and eleven healthy participants. Using Oil-red O staining and immunoblotting, we examined the effects of Gal-9 and free fatty acid (FFA) on lipid accumulation in human hepatocytes and FABP1 expression. Results Serum Gal-9, sTIM-3 and FABP1 level were significantly higher in RA patients (median 5.02 ng/mL, 3.42 ng/mL, and 5.76 ng/mL, respectively) than in healthy participants (1.86 ng/mL, 0.99 ng/mL, and 0.129 ng/mL, all p < 0.001). They were also significantly higher in patients with moderate-to-severe NAFLD compared with none-to-mild NAFLD (p < 0.01; p < 0.05; and p < 0.01, respectively). Serum Gal-9 levels were positively correlated with sTIM-3, FABP1, FABP4 levels, and ultrasound-fatty liver score, respectively, in RA patients. Multivariate regression analysis revealed that Gal-9 (cut-off>3.30) was a significant predictor of NAFLD development, and Gal-9 and sTIM-3 were predictors of NAFLD severity (both p < 0.05). The cell-based assay showed that Gal-9 and FFA could upregulate FABP1 expression and enhance lipid droplet accumulation in hepatocytes. Conclusion Elevated levels of Gal-9 and sTIM3 in RA patients with NAFLD and their positive correlation with NAFLD severity suggest the pathogenic role of Gal-9 signaling in RA-related NAFLD.